Application of Waterflood Characteristic Curves in the Estimation of Recoverable Reserves in the S Block of the Yanchang Oilfield - Liu, Siyao (International Journal of Natural Resources and Environmental Studies, 2025)
Waterflood characteristic curves are essential tools for estimating recoverable reserves in oilfields, accurately representing the dynamics of waterflood development and providing reliable support for reserve evaluations. They offer significant guidance for optimizing development plans and improving resource utilization efficiency. This study focuses on the S block of the Yanchang Oilfield, utilizing production dynamic data from 128 wells. The research systematically applies Type A waterflood characteristic curves and calibrated Type A waterflood characteristic curves to estimate recoverable reserves and predict waterflood recovery factors. The results show that the dynamic geological reserves calculated using the Type A waterflood curve amount to 714.29×104 t, with technical recoverable reserves of 260.49×104 t and a recovery factor of 36.47%. The calibrated Type A waterflood curve (calibration coefficient C=17.10) yields dynamic geological reserves of 1875×104 t, technical recoverable reserves of 613.21×104 t, and a recovery factor of 32.70%. A comparison indicates significant differences in the results of the two methods, primarily due to the calibration curve's adjustment for non-ideal waterflood conditions, such as reservoir heterogeneity and early development data deviations. This study not only enriches the application of waterflood characteristic curves in oilfield development but also provides data support for dynamic evaluation and subsequent optimization of development plans for the S block of the Yanchang Oilfield. It offers valuable insights for the estimation of recoverable reserves in similar waterflood reservoirs.